Computer Generated Caricature: A Survey - Sadimon, S B; Sunar, M S; Mohamad, D; Haron, H (2010 International Conference on Cyberworlds, 2010)
Caricature is a pictorial representation of a person or subject in summarizing way by exaggerating the most distinctive features and simplifies the common features in order to make that subject different from others and at the same time, preserve the likeness of the subject. Computer Generated Caricature is developed in order to assist the user in producing caricature automatically or semi-automatically. It is derived from the rapid advance in computer graphics and computer vision and introduced as a part of computer graphics' non-photo realistic rendering technologies as well. Recently, Computer Generated Caricature becomes particularly interesting research topic due to the advantageous features of privacy, security, simplification, amusement and their explosive emergent real-world application such as in magazine, digital entertainment, Internet and mobile application. On the basis of the previous facts, this paper surveys the uses of caricature in variety of applications, theories and rules in the art of drawing caricature, how these theories are simulated in the development of caricature generation system and the current research trend in this field. Computer generated caricature can be divided into two main categories based on their input data type: human centered approach and image processing approach. Next, process of generating caricature from input photo is explained briefly. It also reported the state of the art techniques in generating caricature by classifying it into four approaches: interactive, regularity-based, learning-based and predefined database of caricature illustration. Lastly, this paper will discuss relevant issues, problems and several promising direction of future research.